Research on Vibration and Noise Coupling Characteristics of Bogie Gearboxes for Metro Vehicles - Ni Jinshang (Jixie chuandong)
Aiming at the common key issues for gearbox vibration and noise, a certain type of subway car bogie gearbox has been regarded as the research object. The rigid-flexible coupling dynamics and vibration noise simulation model of the gearbox have been established by the LMS Virtual Lab software. The variable meshing stiffness, the dynamic bearing supporting load, the gearbox vibration, and the structural noise in the vicinity of the gearbox have been simulated and analyzed, and the vibration of the gearbox and the structural noise in the vicinity of the gearbox have been tested and verified. The results show that the time-varying meshing force of the helical gear pair of the subway car bogie gearbox and the dynamic load of the supporting bearing show a periodic fluctuation trend above and below a certain average value; the vibration of the gearbox body and the structural noise in the vicinity of the gearbox in the up and down, left and right direction are greater than those in the axial direction; the maximum relative errors between the simulated and experimental values of vibration and structural noise are respectively 14.61% and 3.77%, which can verify the rationality and correctness of the simulation analysis. The research provides a vibration and noise reduction for the theoretical basis and technical supporting of the subway vehicles and gearboxes.